(untitled) (مجلة البحوث الأكاديمية, 2025)
Hyphaene thebaica (HT), also known as the "Doum palm" belonging to family Aceraceae, is a palm tree native to Africa. Aims: The current study sought to evaluate the anxiolytic-like activities, antidepressant, analgesic and properties of (DPME) and (DPAE) in stressed mice. Experimental design: The study was experimental research designed to include four lines: extraction of the plant materials, evaluation of anxiety using three tests: HCT, OFT, and LDBT, while the depressant activity is assessed by TST. The efficacy of the DPME and DPAE-mediated antidepressant and anxiolytic activities was compared with the control groups, diazepam (1 mg/kg, i.p) as an anxiolytic drug, and fluoxetine (20 mg/kg, p.o.) as an antidepressant drug evaluation of peripheral analgesic activities of DPME and DPAE using the chemical method (acetic acid 1%, i.p.). The fourth line was an assessment of the effect of DPME on PILO (280 mg/kg)-induced convulsions. The study was carried out using Albino mice (30±5 g) of either sex, which were divided into several groups with six mice each.